The Role of Competence on The Leadership Effect on Employee Performance of Micro, Small and Medium Enterprises - Rumijati, Aniek (Jurnal Bisnis dan Manajemen, 2021)
This study aims to describe leadership, competence, and employee performance; analyze the influence of leadership on employee performance in Micro Small Medium Enterprises (MSMEs) both directly and through employee competence as a mediating variable. Data collection used a survey method, with a questionnaire as a tool. The population is employees in MSMEs. The sampling technique used purposive sampling with a total of 83 respondents. The analytical method used is a Scale Range and path analysis with the Smart PLS3 program. The results of the study showed that leadership is very good, the competence and performance of employees are very high; leadership has a significant effect on employee performance directly, as well as through competence mediation variables.